Synthesis and Biological Evaluation of New 1,3,4-Oxadiazoles as Potential Anticancer Agents and Enzyme Inhibitors - Yurttaş, Leyla; Çavuşoğlu, Betül K.; Çiftçi, Gülşen A.; Temel, Halide E. (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: 1,3,4-Oxadiazoles have been known with a wide variety of pharmacological activities including anticancer activity. Objective: In this study, novel 2,5-disubstituted 1,3,4-oxadiazole derivatives were synthesized and evaluated for determining their anticancer, anticholinesterase and lipoxygenase (LOX) inhibitory activity. Methods: All compounds were tested against C6 rat glioma, A549 human lung carcinoma and NIH/3T3 mouse embryo fibroblast cell lines to define cytotoxic concentrations and apoptosis induction levels which they cause. Results: Many of the compounds exhibited remarkable potency that compounds 2a, 2b, 2e, 2h and 2j against C6 cells and compounds 2a, 2b, 2d, 2g, 2i, 2j against A549 cells were found more active than cisplatin. Compound 2d namely, 2-[(5-(4-aminophenyl)-1,3,4-oxadiazol-2-yl)thio]-1-(4-chlorophenyl)ethan-1-one induced apoptosis of A549 cells with 74.9% whereas cisplatin caused 70.9% percentage. Conclusion: Among them, compounds 2d and 2j against A549 cell line, compounds 2b and 2e against both tumor cell lines showed selective cytotoxicity evaluating the inhibition concentration against NIH/3T3 cell line. None of the compounds showed significant acetylcholinesterase (AChE) and lipoxygenase inhibitory activities.
Keywords: Heteroaryl